Cargo accumulation risks in maritime supply chains: A new perspective towards risk management for theory, and recommendations for the insurance industry and cargo shippers - Stephan L. K. Freichel; Johannes K. Wörtge; Arthur Haas; Lars ter Veer (Logistics Research, 2022)
Global supply chains are becoming increasingly complex with many players involved, reducing visibility and control of commodity flows. The majority of worldwide goods flows are distributed by sea, which means that ever greater vessels and ever greater ports play a central role in Supply Chain Management. Hence, increasingly large quantities of goods and hazardous substances accumulate stationary and mobile at these locations. The natural riskiness of maritime distribution is heightened since a large number of shipments are simultaneously determined by only one risk event. In this paper, the currently under- researched phenomenon of accumulation risk (AR) is investigated, using a qualitative-explorative research approach. Based on the relevant scientific and practical literature, AR is first defined and characterized against the background of Supply Chain Risk Management (SCRM). Subsequently, 23 interviews with a total of 34 experts from the insurance industry and various cargo-shipping industries were conducted and analyzed using qualitative content analysis (QCA). In this way, the current practices regarding AR handling of maritime insurers and cargo shippers were identified. Moreover, challenges hindering and opportunities enabling better risk identification, assessment, and management are explored. Lastly, an outline for future risk management and monitoring tool is established. Hereby, a theoretical contribution to research is made and grounded in the four phases of SCRM by adding a new perspective on maritime supply chain risk. Likewise, practitioners in the insurance industry and users of maritime distribution networks will find concrete recommendations on how to deal with AR.
Keywords: 650; Accumulation Risks; Supply Chain Risk Management; Global Supply Chains; SupplyChain Insurance